2013
DOI: 10.5009/gnl.2013.7.3.270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cellular Senescence in the Gastrointestinal Mucosa

Abstract: Cellular senescence is a biologically irreversible state of cell-growth arrest that occurs following either a replicative or an oncogenic stimulus. This phenomenon occurs as a response to the presence of premalignant cells and appears to be an important anticancer mechanism that keeps these transformed cells at bay. Many exogenous and endogenous triggers for senescence have been recognized to act via genomic or epigenomic pathways. The most common stimulus for senescence is progressive loss of telomeric DNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…AGE are reported to be related to the prognosis and severity of heart failure, and predict cardiovascular disease mortality in older adults, which contribute to the increased myocardial stiffening of aging through cross‐linking elastin and collagen, and the development of cardiac fibrosis, promoting accumulation of collagen, stimulating inflammation and oxidative stress mediated by its receptor, RAGE . In the present study, we found that the activity of SA‐β‐Gal, a useful biomarker for cell senescence, was upregulated by AGE in rat cardiac fibroblasts. Furthermore, increased expression of P16 protein was detected in AGE‐treated cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 60%
“…AGE are reported to be related to the prognosis and severity of heart failure, and predict cardiovascular disease mortality in older adults, which contribute to the increased myocardial stiffening of aging through cross‐linking elastin and collagen, and the development of cardiac fibrosis, promoting accumulation of collagen, stimulating inflammation and oxidative stress mediated by its receptor, RAGE . In the present study, we found that the activity of SA‐β‐Gal, a useful biomarker for cell senescence, was upregulated by AGE in rat cardiac fibroblasts. Furthermore, increased expression of P16 protein was detected in AGE‐treated cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 60%
“…Both chronic inflammation and ongoing exposure to an acid and bile containing gastroesophageal refluxate are considered to be important pathogenic factors in the development of BE and EAC [3][4][5]. Toll-like receptor (TLR) 2 signalling and lysosomal function have been linked to inflammation associated carcinogenesis [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In BE and upper gastrointestinal cancer, including EAC, altered lysosomal function and activity and expression of factors involved in the lysosomal pathway have been reported [6,7,9,10]. Lysosomes are intracellular organelles that are known to be involved in processing waste products and are important regulators in intracellular homeostasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the gut, this pathway prevents the development of various gastrointestinal cancers. 14 In contrast, sirtuin signaling delays senescence and further prolongs cellular life expectancy. 15 Members of the sirtuin family have been connected to obesity and related comorbidities, and in recent literature, connected to inflammation.…”
Section: Discussionmentioning
confidence: 99%